Beveridge's rival: Juliet Rhys-Williams and the campaign for basic income, 1942–55. Issue 2 (2nd April 2016) - Sloman, Peter
Abstract: Historians of Britain's post-war welfare state have long been aware of the shortcomings of the social insurance model, but the political impact of the Beveridge report has tended to obscure the alternative visions of welfare canvassed in the 1940s and 1950s. This article examines the social activist Juliet Rhys-Williams' campaign for the integration of the tax and benefit systems and the provision of a universal basic income, which attracted wide interest from economists, journalists, and Liberal and Conservative politicians during and after the Second World War. Though Rhys-Williams' proposals were not adopted, they helped establish a distinctive 'social market' perspective on welfare provision which has become central to British social policy debates since the 1960s and 1970s.